FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN BEROBAT PADA PASIEN HIPERTENSI - Sada, Fidy Randy; Santoso, Raden Bagus Edy; Yulianita, Yulianita; Rondonuwu, Rolly (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Hypertension is one of the most common medical conditions encountered in primary health care in many parts of the world. Patient compliance and non-compliance in undergoing treatment can affect patient recovery. The purpose of the study was to determine the factors associated with the level of treatment compliance in hypertensive patients. The research design used in this study was cross sectional. The research was conducted at the Tanakeke Health Center Work Area in July 2024. The population is all hypertensive patients who come for treatment to the Health Center totaling 198 people. The sample amounted to 66 people. The sampling technique used in this study was purposive sampling. Data analysis was carried out univariate and bivariate. The results showed a relationship between family support (p value: 0.000) and treatment motivation (p value: 0.000). It is recommended for the patient's family to provide support and motivation to patients with hypertension, so that the patient has the enthusiasm to recover.Keywords: Hypertension, Family, Motivation